Introduction to Project 2007 - Miles, Timothy; Safari eBooks ([S.l.] : CompuWorks, 2013)
"This course gives the user a beginning orientation to Microsoft Project 2007. The primary focus of this course is to teach the user how to properly use Project 2007 by leveraging the different tools within the application. This includes creating new projects and calendars, entering tasks and relationships, managing resources and learning how to use the variety of tools available to effectively implement a project plan."--Resource description page.
Title from title screen.
Publication information taken from resource description page (viewed August 26, 2013).
Presenter, Timothy Miles.
Keywords: Microsoft Project; Project management -- Computer programs; Electronic books